The Potential Impact of the Global Financial Crisis on World Trade - McKibbin, Warwick J.; Stoeckel, Andrew (2012)
This paper models the global financial crisis as a combination of shocks to global housing markets and sharp increases in risk premia of firms, households and international investors in a global economic model. The model has six sectors of production and trade in 15 major economies and regions. The paper shows that the shocks observed in financial markets can be used to generate the severe economic contraction in global trade and production experienced in 2009. In particular the distinction between the production and trade of durable and non durable goods plays a key role in explaining the much larger contraction in trade than GDP experienced by most economies. The paper explores the implications of the large increase in fiscal deficits and the implications of a global trade war in response to the financial crisis.